Conceptualizing technology influence on job characteristics and work outcomes of instructors in institutions of higher learning - Juhdi, Nurita; Ab Hamid, Ahmad Zohdi (2008)
This article conceptualized the framework of the possible impact of using different levels of technology on the roles and responsibilities of instructors in institutions of higher learning. Based on the literature reviewed, there is an indication that employees who use different types of technology in performing their tasks experience different degree of job attributes. This resulted in different levels of personal and work outcomes. This paper aims to examine any similar relationships among instructors who use different levels of instructional technology by employing Hackman and Oldham’s (1980) JDS instrument to measure core job characteristics and work outcomes. A conceptual framework and several propositions speculating the relationships between levels of technology, job characteristics and work outcome were forwarded.